3.120. Rozwiąż równanie: a) 8x – 2x * (3x – 1) = 2x ^ 2 + 3 c) (2x – 4)(2x + 4) = (3x – 1) ^ 2 – 16 e) (x ^ 2 – 3x + 1)(x + 2) = x ^ 3 – 2x – 1 b) x ^ 2 – 5x + 9 = 63 – (x – 3)(x + 3) d) 6 – (1 – x) ^ 2 = (2x – 3) ^ 2 – (3x + 2) ^ 2 f) (2x – 3)(3x + 5) = (3 – 2x)(x + 3)

3.120. Rozwiąż równanie: a) 8x – 2x * (3x – 1) = 2x ^ 2 + 3 c) (2x – 4)(2x + 4) = (3x – 1) ^ 2 – 16 e) (x ^ 2 – 3x + 1)(x + 2) = x ^ 3 – 2x – 1 b) x ^ 2 – 5x + 9 = 63 – (x – 3)(x + 3) d) 6 – (1 – x) ^ 2 = (2x – 3) ^ 2 – (3x + 2) ^ 2 f) (2x – 3)(3x + 5) = (3 – 2x)(x + 3)